Effects of tamoxifen and aromatase inhibitors on the risk of acute coronary syndrome in elderly breast cancer patients: An analysis of nationwide data. (December 2020) - Choi, Sung Hyouk; Kim, Kyoung-Eun; Park, Yujin; Ju, Young Wook; Jung, Ji-Gwang; Lee, Eun Shin; Lee, Han-Byoel; Han, Wonshik; Noh, Dong-Young; Yoon, Hyung-Jin; Moon, Hyeong-Gon
Abstract: Background: Aromatase inhibitors (AIs) are the preferred endocrine treatment for postmenopausal hormonal receptor-positive breast cancer. However, there is controversy on the long-term cardiovascular and cerebrovascular safety of AIs over that of tamoxifen. Methods: We analyzed the National Health Information Database (NHID) of 281, 255 women over a 20-year-old diagnosed with breast cancer between 2009 and 2016. Cardiovascular events (CVEs) were defined as the development of the following, acute coronary syndrome (ACS), ischemic and hemorrhagic stroke, defined by using insurance claim records. The model was constructed by Cox proportional hazard regression and this model was used to analyze the effects of AI and tamoxifen on CVE. Results: We included 47, 569 women for the final analysis. Patients were classified into 'No hormonal treatment (n = 18, 807), 'Switch ( n = 2097)', 'Tamoxifen ( n = 7081)' and 'AI ( n = 19, 584)'. There were 2147 CVEs in 2032 patients (4.1%). Univariate analysis showed that women with tamoxifen had significantly lower risk for CVEs compared to no-treatment (hazard ratio (HR) 0.84, 95% confidence interval (CI) 0.74–0.97) while AI showed no such effect (HR 0.93, 95% CI 0.84–1.02). After adjusting for other risk factors (hypertension, dyslipidemia, family history), the use of tamoxifen was associated with significant protective effect against ACS (HR 0.63, 95% CI 0.47–0.84). Conclusions: Our results, based on the NHID, supports the protective effect of tamoxifen against CVE in Korean breast cancer patients aged 55 and older that is not seen with AIs. Our results can guide the selection of adjuvant hormonal treatment agents for Korean breast cancer patients based on their risk of developing CVE. Highlights: Controversy on the long-term cardiovascular and cerebrovascular safety of AIs over that of tamoxifen. The protective effect of tamoxifen against cardiovascular events in elderly breast cancer patients that is not seen with AIs. Choice of hormonal therapy depends on patient's cardiovascular or cerebrovascular risks.